2-(3,5-Di-tert-butyl-4-hydroxybenzylsulfanyl)nicotinic acid - Mansor, S.; Yehye, Wageeh Abdulhadi; Ariffin, Azhar; Abd Rahman, Noorsaadah; Ng, Seik Weng (International Union of Crystallography, 2008)
Two mol-ecules of the title compound, C(21)H(27)NO(3)S, are disposed about a center of inversion, generating an O-H⋯O hydrogen-bonded dimer.